(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2000)
A generalized version of the declarative semantics of Horn clause programs on abstract structures is presented. The amin feature of the semantics is that it does not admit searching in the domain of the structure.